Custo da rotatividade da equipe de enfermagem em hospital de ensino - Ruiz, Paula Buck de Oliveira (2014)
Introduction: The staff turnover is determined by the output of employees or exchanges of staff the organization and constitutes a poorly explored subject and subdued by the institutions, but it begins to take relevant due to the economic consequences. The management of this indicator may benefit the intellectual capital, the environment, the institution's image and cost control. Aims: Identify the types and reasons of dismissals of professionals and calculate the rate and cost of staff turnover. Methods: Study was exploratory, descriptive, and manner of case study, conducted in teaching hospital southeastern Brazil, in the period May-November 2013. The data were obtained through interviews shutdown provided by human resources in the period 2009-2012. For the calculation of the turnover was used the equation proposed by the Hospital Quality Commitment. For the measurement of cost, the collection was prospective (May-August 2013). and was used the Methodology of Calculation of Cost of Turnover in Nursing. The pre and post contract processes were mapped and the direct costs of labor were analyzed Results: There were 522 dismissal, the average of terminations was 76.3 (dp 97,3), personal reason was the predominant cause of shutdowns - 35.9%, mainly for nursing assistants. The average turnover rate/year was 9.4% nurses, 35.7 % and 11.2 % technical assistants. The total cost of turnover, during the period of 2013 May and August was R$314,605.62 and the average was R$2.759,69, and the cost of employees was R$8.279,09 (average turnover rate of 0.98%). The costs of pre-employment totaled R$101.004,60, and the vague process consumed – 29.5%, and the costs of post-employment totaled R$213.601,02, aimed mainly at subprocess decreased productivity – 63.6%. The cost of turnover/employee avarage R$2.221,42 to R$3.073,23 and the cost of dismissal/employee was R$8.279,09, from R$5.553,56 to R$16.811,75. Conclusion: This research showed a historical series regarding turnover and reasons for dismissals, as well as the financial impact of employees/off cost which represented three times the average salary of the nursing staff. These findings instrumentalize manager for improvement in reducing costs of these proceedings and directed will retain intellectual capital policies.